Четверогласие стихий: [стихотворения] / Константин Бальмонт - Бальмонт Константин Дмитриевич (Великие поэты, 2013)
Экземпляры: ф.6 (20210401) / Инвентарный номер: 3674zzz / Цена: / Сис.шифр: 84(2Рос=Рус)1-5 / Авт.знак: Б 21 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)1-5